2012
DOI: 10.1007/s00264-012-1557-y
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the radiation risk from fluoroscopic-assisted arthroscopic surgery of the hip

Abstract: Purpose The purpose of the study was to quantify patient exposure to ionising radiation during fluoroscopic-assisted arthroscopic surgery of the hip, establish a risk profile of this exposure, and reassure patients of radiation safety during the procedure. Methods We retrospectively analysed the dose area products for 50 consecutive patients undergoing arthroscopic hip surgery by an experienced hip arthroscopic surgeon. The effective dose and organ dose were derived using a Monte Carlo program. Results The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Median DAP for hip procedures ranged from 0.64 Gy-cm 2 for hip injection to 2.65 Gy-cm 2 for insertion of cannulated hip screw. Budd et al reported exposure associated with fluoroscopically guided hip arthroscopy and noted a mean DAP of 2.97 Gy-cm 2 [12]. Our median DAP was 0.72 indicating that on the spectrum of hip related procedures fluoroscopically guided DA-THA involves relatively little radiation exposure, only slightly exceeding that associated with hip injection ( Table 2).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Median DAP for hip procedures ranged from 0.64 Gy-cm 2 for hip injection to 2.65 Gy-cm 2 for insertion of cannulated hip screw. Budd et al reported exposure associated with fluoroscopically guided hip arthroscopy and noted a mean DAP of 2.97 Gy-cm 2 [12]. Our median DAP was 0.72 indicating that on the spectrum of hip related procedures fluoroscopically guided DA-THA involves relatively little radiation exposure, only slightly exceeding that associated with hip injection ( Table 2).…”
Section: Discussionmentioning
confidence: 43%
“…The patient group assessed was relatively small and heterogeneous. However, with a total of 52 patients undergoing the same surgical procedure, our sample size is on par with previously published studies assessing radiation exposure in other orthopedic procedures [10,12,13]. Furthermore, in addition to mean DAP, fluoroscopy time and surgeon dose, we calculated the impact of various patient and surgery specific variables on exposure level.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with fluoroscopy-guided injections, US-guided injections decrease the radiation burden to both the patient and the provider. While recent studies have suggested that fluoroscopy-assisted arthroscopic surgery of the hip is safe, with relatively low radiation dosing, 3 , 13 it stands to reason that any radiation exposure is an occupational health hazard. There are also financial incentives to performing US-guided injections in the office setting: the facility relative value unit in 2016 was 1.77 for a US-guided hip injection compared with the nonfacility relative value unit of 2.60.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that it is unlikely that radiation exposure during fluoroscopy-assisted hip arthroscopy is high enough to cause health risks to the surgeon or patient. 21,22 However, a recently published study identified a lack of knowledge of radiation safety among orthopedic surgeons treating patients with FAI and reveals the need for greater education about this subject. 23 Nogier et al 24 recently described a hip arthroscopy technique that eliminates the use of intraoperative fluoroscopy to reduce complications.…”
Section: Discussionmentioning
confidence: 99%